Industry Specific Multipliers to Identify Key Industries of Indian Economy: An Application of Input Output Analysis (Global Journal of Human-Social Science, 2017)
Abstract not found
Keywords: key industries; input output analysis; interindustry tables; leontief model; output multiplier; employment multiplier; type i multiplier; type ii mult